1996
DOI: 10.1088/0741-3335/38/4/002
|View full text |Cite
|
Sign up to set email alerts
|

MHD-mode stabilization by plasma rotation in TEXTOR

Abstract: An experimental investigation into rotating MHD modes has been performed in the TEXTOR tokamak. The effects on the stability of the MHD tearing modes of coupling between m/n = 2/1 and 1/1 modes and of the slowing down of the mode rotation by wall friction have been studied. Tangential neutral beam injection (NBI) has been used to change the toroidal rotation to observe the influence of plasma rotation on the development of MHD modes.Two phases in the rotation frequency behaviour of the modes can be distinguish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 12 publications
1
46
0
Order By: Relevance
“…As the poloidal harmonic of this exponentially growing n = 1 field is unknown, in principle it is possible that the 2/1 island is unchanging, while an m = 1 or m = 3 instability is appearing and growing. Coupling of the 2/1 and 3/1 modes has been observed on ASDEX-Upgrade [44] and investigated in numerical studies [45], while coupling of the 2/1 and m/n = 1/1 has been observed on TEXTOR [46], the RTP Tokamak [14], and studied in simulations [41]. Although m = 4 might be a candidate for this growth in some shots, it will be shown in section 8 that more than half of the disruptive discharges have q 95 < 4, so it could only explain a minority of cases.…”
Section: Distributions Of Irlm Toroidal Phase At Lockingmentioning
confidence: 99%
“…As the poloidal harmonic of this exponentially growing n = 1 field is unknown, in principle it is possible that the 2/1 island is unchanging, while an m = 1 or m = 3 instability is appearing and growing. Coupling of the 2/1 and 3/1 modes has been observed on ASDEX-Upgrade [44] and investigated in numerical studies [45], while coupling of the 2/1 and m/n = 1/1 has been observed on TEXTOR [46], the RTP Tokamak [14], and studied in simulations [41]. Although m = 4 might be a candidate for this growth in some shots, it will be shown in section 8 that more than half of the disruptive discharges have q 95 < 4, so it could only explain a minority of cases.…”
Section: Distributions Of Irlm Toroidal Phase At Lockingmentioning
confidence: 99%
“…Plasma rotation is one of the central topics for toroidal plasma confinement and it is considered to play a key role in tokamak plasma performance. Plasma rotation can have a strong impact on plasma stability and confinement of fusion plasmas, through its ability to stabilize MHD modes [1], affect the strength of transport barriers [2], affect turbulence stabilization due to E Â B shear [3], and reduce the profile stiffness in the presence of anomalous transport [4]. In present day experiments, rotation is often driven by the torques of neutral beam injection (NBI), while in an alpha-heated reactor the momentum input is expected to be small [5].…”
mentioning
confidence: 99%
“…This motivates further investigation of up-down asymmetric devices because significant momentum transport has been shown to improve tokamak performance. Experiments on DIII-D [18,19] and TEXTOR [20] (among others) used plasma rotation to stabilize resistive wall modes, a dangerous MHD instability, and enable discharges with plasma beta that exceeded the Troyon limit [21]. Additionally, a gradient in rotation is theoretically expected to decorrelate turbulence and directly reduce energy transport [22].…”
Section: Introductionmentioning
confidence: 99%